ERSTIMATING INDONESIA'S CORPORATE INCOME TAX POTENTIAL 2006-2010 - Reko Anjariadi (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2011)
Indonesia's tax ratio is low compared to other countries. the importance of tax is unarguable. Currently, tax revenue contributes 70% of the state budget. it is necessary to know how large the tax potential from the indonesian economy actuallyis. Since corporate income tax is the highest contributor of tax revenue , it is important to calculate the tax potential using many diffrent approaches. This study tries to give alternatives in estimating the corporate income tax potential by using input-output analyses. an operating surplus in the input-output table is considered as a proxy af taxable income. By using impact analysis and the leontief inverse, the author forecasts an operating surplus for years 2006-2010 based the 2005 input-output table. Another important tool is an adjusment on the effective tax rate , since it is unrealistic if using statutory tax. Furthermore, there are several main sectors that still have room for collecting taxes as follows: processingsectors, financial and real estate sectors, transfortationand communication sectors, trade hotel and restaurant sectors non oil and gas mining sectors, and other services sectors . This study proposes that indonesia has the potential to achieve a higher tax ratio in the near future